Factors affecting the attitudes of students towards learning English as a foreign language - Addisu Sewbihon Getie (Cogent Education, 2020)
This study aimed at investigating on factors affecting the attitudes of grade 10 students towards learning EFL in Debremarkos Comprehensive Secondary School in Debre Markos town, Ethiopia. The researcher randomly selected 103 sample students (10%) out of the total population (1030) for the study. In order to gather data, a questionnaire was carefully and systematically adapted and designed. Nine sample students were also selected purposely for focus group discussion, and Grade 10 English teachers were selected for the interview. Then, the data were analyzed quantitatively and qualitatively. The findings of the study mainly showed that the attitudes of grade 10 students towards learning EFL is positive. There are social factors (e.g., English native speakers, peer groups and learners’ parents) affecting students’ attitudes positively. On the other hand, educational context factors like English language teachers, the English language learning situations (e.g., the classrooms, arrangements of seats and the physical learning environment) had negative impacts on students’ attitude. However, the findings showed that target language learners have positive attitudes towards the other educational context factor that is the English textbook of grade 10 which means English as a foreign language teaching materials in the study’s context affect students’ attitudes positively. By lowering the psychological variables (i.e. affective filters) for the target language learners, it is possible to aid the language learning process. Thus, as the implication of this study considers, the physical learning environment should be improved, and to achieve this, the government should work in conjunction with the school principals, teachers and societies.